Quality of friendships and motivation to change in adolescents with Anorexia Nervosa. (August 2016) - Malmendier-Muehlschlegel, Anja; Rosewall, Juliet K.; Smith, Jared G.; Hugo, Pippa; Lask, Bryan
Abstract: This study explored the relationship between quality of friendships, motivation to change and peer support among young people receiving inpatient treatment for Anorexia Nervosa (AN). Thirty participants were recruited from three inpatient wards. Questionnaires assessed motivational stage, friendship functions and characteristics of friendships specific to AN. Three friendship functions - Help, Intimacy and Self-Validation - were significantly and positively correlated with greater motivational stage. Describing friends on the ward as supportive of adherence to the treatment program was positively associated with greater motivational stage and higher quality friendships. The association between motivation, friendship quality and peer support in treatment identifies close and supportive friendships among young people with AN as a potential target to improve outcomes. Highlights: Friendships between young people with Anorexia Nervosa have positive and negative dimensions. In this study, quality of ward friendships and peer support were positively associated with motivation to change. Focus should be given to building healthy friendships in eating disorder inpatient treatment programs. Supportive friendships among young people with Anorexia Nervosa should be explored as a treatment target to improve outcomes.